Автоматизированный стенд для оцифровки данных о метеорных исследованиях - Шандренко, Р. В. (ХНУРЭ, 2012)
In paper presents an automated device for converting data of meteor radiolocation observations from the film into digital format. The device created by the author of this work. Impossibility to use serial devices is shown. Hard and soft parts of an automated device are presented. Is shown high speed and accuracy of the device work.